Environmental and Ecological Statistics - Dutilleul, Pierre; Manly, Bryan F.J.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Environmental and Ecological Statistics publishes papers on practical applications of statistics and related quantitative methods to environmental science addressing contemporary issues. Emphasis is on applied mathematical statistics, statistical methodology, and data interpretation and improvement for future use, with a view to advance statistics for environment, ecology and environmental health, and to advance environmental theory and practice using valid statistics. Besides clarity of exposition, a single most important criterion for publication is the appropriateness of the statistical method to the particular environmental problem. The Journal covers all aspects of the collection, analysis, presentation and interpretation of environmental data for research, policy and regulation. The Journal is cross-disciplinary within the context of contemporary environmental issues and the associated statistical tools, concepts and methods. The Journal broadly covers theory and methods, case studies and applications, environmental change and statistical ecology, environmental health statistics and stochastics, and related areas. Special features include invited discussion papers; research communications; technical notes and consultation corner; mini-reviews; letters to the Editor; news, views and announcements; hardware and software reviews; data management etc.
Keywords: Ecology; Environmental sciences; Ecology; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Math. Appl. in Environmental Science; Statistics for Life Sciences, Medicine, Health Sciences; Theoretical Ecology/Statistics.